Occurrence and Timing of Advance Care Planning in Persons With Dementia in General Practice: Analysis of Linked Electronic Health Records and Administrative Data - Azizi, Bahar; Tilburgs, Bram; van Hout, Hein P. J.; van der Heide, Iris; Verheij, Robert A.; Achterberg, Wilco P.; van der Steen, Jenny T.; Joling, Karlijn J. (Frontiers in Public Health, 2022)
Background Advance care planning is a process where goals and preferences for future treatment and care are discussed. For persons with dementia, it is crucial to timely engage in ACP. Therefore, we study advance care planning in dementia using electronic health record data. This study aims to determine how often advance care planning conversations are recorded, analyze time from dementia diagnosis until the first recorded conversation and time from the first recorded conversation to death, and analyze which factors are associated with the timing of advance care planning. Methods Electronic records of 15,493 persons with dementia in general practice between 2008 and 2016 were linked to national administrative databases. Advance care planning conversations and indicators of health deficits to determine frailty were obtained from electronic records coded with the International Classification of Primary Care. Socio-demographic characteristics were derived from the national population registry managed by Statistics Netherlands. Date of death was derived from the Personal Records Database (2008 to 2018). Results Advance care planning was recorded as such as 22 (95% CI, 20-23) first conversations per 1,000 person-years of follow-up. The hazard ratio (HR) for the first conversation increased every year after dementia diagnosis, from 0.01 in the first year to 0.07 in the 7th and 8th year after diagnosis. Median time from a first conversation to death was 2.57 years (95% CI, 2.31-2.82). Migrant status (non-Western versus Western (HR 0.31, 95% CI, 0.15-0.65)) was significantly associated with a longer time from dementia diagnosis to the first conversation. Being pre-frail (HR 2.06, 95% CI, 1.58-2.69) or frail (HR 1.40, 95% CI, 1.13-1.73) versus non-frail was significantly associated with a shorter time from dementia diagnosis to the first conversation. Conclusion Advance care planning conversations in Dutch general practice were rare for persons with dementia, or was rarely recorded as such. In particular among persons with a non-Western migration background and those who are non-frail, it started long after diagnosis. We advise further research into public health and practical strategies to engage persons with dementia with a non-Western migration background and non-frail persons early in the disease trajectory in advance care planning.